Decreasing the Number of Leukocytes as an Effect of Standard Therapy and Rhodomyrtus tomentosa Leaves Extract Therapy - Noviani, Doris; Yulianti, Ika; Ariyanti, Ririn; Lesmana, Hendy; Rahman, Muhammad Saiful; Rasdiana, Rasdiana; Sari, Maya (Baiman Bauntung Batuah Center, 2024)
The postpartum period is a vulnerable period to infection due to low immunity. An increase in leukocytes characterizes the body's response to infection; several leukocytes close to normal values indicate that the infection period will end. The research objective was to determine the effectiveness of Rhodomyrtus tomentosa leaf extract on the number of leukocyte cells in mothers with postpartum infections at Tarakan City General Hospital. The research used an Analytical survey with a sample of postpartum mothers who came to the Tarakan City General Hospital (April-August 2022). Criteria for Group 1 were mothers with postpartum infections and had not been given any therapy; Group 2 were healthy postpartum mothers; Group 3 were mothers with postpartum infections who were given standard therapy; Group 4 is mothers with postpartum infections who were given standard therapy and on the doctor's advice the day before they were given Karamunting leaf extract as additional therapy. The research results show that giving Rhodomyrtus tomentosa leaf extract with standard therapy reduces the number of leukocytes to close to normal values, so it can be concluded that it has an anti-inflammatory effect on mothers with postpartum infections. Further clinical trial research is needed with adequate samples and more uniform conditions for each sample.